Plant-Growth Promoting Bacillus oryzicola YC7007 Modulates Stress-Response Gene Expression and Provides Protection From Salt Stress - Baek, Dongwon; Rokibuzzaman, Mohammad; Khan, Ajmal; Kim, Min Chul; Park, Hee Jin; Yun, Dae-jin; Chung, Young Ryun (Frontiers in Plant Science, 2020)
High salt stress caused by ionic and osmotic stressors eventually results in the suppression of plant growth and a reduction in crop productivity. In our previous reports, we isolated the endophytic bacterium Bacillus oryzicola YC7007 from the rhizosphere of rice (Oryza sativa L.), which promoted plant growth and development and suppressed bacterial disease in rice by inducing systemic resistance and antibiotic production. In this study, Arabidopsis thaliana seedlings under salt stress that were bacterized with YC7007 displayed an increase in the number of lateral roots and greater fresh weight relative to that of the control seedlings. The chlorophyll content of the bacterized seedlings was increased when compared with that of untreated seedlings. The accumulation of salt-induced malondialdehyde and Na+ in seedlings was inhibited by their co-cultivation with YC7007. The expression of stress-related genes in the shoots and roots of seedlings was induced by YC7007 inoculation under salt stress conditions. Interestingly, YC7007-mediated salt tolerance requires SOS1, a plasma membrane-localized Na+/H+ antiporter, given that plant growth in sos2-1 and sos3-1 mutants was promoted under salt-stress conditions, whereas that of sos1-1 mutants was not. In addition, inoculation with YC7007 in upland-crops, such as radish and cabbage, increased the number of lateral roots and the fresh weight of seedlings under salt-stress conditions. Our results suggest that B. oryzicola YC7007 enhanced plant tolerance to salt stress via the SOS1-dependent salt signaling pathway, resulting in the normal growth of salt-stressed plants.